دراسة عامل الصفاء الجوي في مدينة الناصرية - MOHAND A. Ali (مجلة علوم ذي قار, 2019)
Clearness index in al-Nasseria city at longitude (31.15) and latitude (46.14) during 2009 was evaluated to explore the solar radiation arriving the Earth surface, as will as the impact of solar energy on the other meteorological parameters including relative humidity, temperature average, the relative number of sunshine hours. The mathematical relations were deduced to describe such relations. All relations were linear, which indicates that the maximum clearness index was at summer and has a value of (0.60.3). The effect was attributed to the absorption, scattering for incoming solar beam during its